Asking your phone or a frontline employee? The influence of in‐store information source on choice overload, responsibility, and confidence among young consumers - Schäfers, Tobias; Kessenbrock, Andreas; Cziehso, Gerrit; Kukar‐Kinney, Monika (Psychology & Marketing)
Abstract - Consumers frequently use mobile phones in a store to search for external information as an alternative to consulting with frontline employees. Mobile phone usage is especially prevalent among young consumers. Drawing on qualitative study results and existing literature, we conceptualize the effects of different in‐store information sources on choice overload, responsibility, and confidence among young consumers, as well as the moderating role of product category knowledge. A field experiment suggests that when knowledge is low, consulting with frontline employees (vs. mobile phone) leads to lower choice overload and, consequently, increases choice confidence. When knowledge is high, these beneficial effects are attenuated. At the same time, young consumers perceive greater choice responsibility when their phone is the information source; however, this does not influence choice confidence. This work contributes to extant literature by extending the knowledge of customer experience at the point of sale, the role of technology usage in in‐store retailing, and the role of frontline employees as an information source. It also provides managerial implications for retailers by highlighting the importance of providing an opportunity for an in‐person frontline employee interaction especially when customers have low product category knowledge.